Guru Sibaso and Gendang Karo in Gendang Perumah Begu - Ramanta Alkaro Sinulingga; Diaspita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to determine the form of the Karo drum and guru sibaso in the perumah begu drum. This article uses a qualitative descriptive research method, because in this research the data produced is descriptive data obtained from data in the form of writing, audio recordings, video recordings or from trusted informant sources. The data collection techniques used are observation, interviews and documentation. The research instruments needed are stationery notes and recording equipment, both audio and video. This article also explains the function of the drum and guru sibaso in the perumah begu drum and its contents, namely the function of emotional expression and the function of cultural continuity.